A Sentimental Study of Learning: Does Gamification in Learning Support Elementary School Students’ Autonomy? - Arpiani; Rahmadani; Indri; Zaenal Abdul Jaelani (Program Studi PGSD Universitas Madako Tolitoli, 2025)
Gamification is expected to enhance students’ motivation, engagement, and understanding in the process of self-directed learning in the digital era. This study aims to analyze students’ sentiments toward the use of gamification-based learning platforms in supporting independent learning at the elementary school level. The research was conducted at SDN 1 Sibaluton, involving 20 sixth-grade students as subjects. The methods employed included observation, questionnaires, interviews, and student worksheets, while data analysis was carried out using the Miles and Huberman model through stages of data collection, reduction, presentation, and conclusion drawing. The results indicate that approximately more than 85% of students held positive sentiments toward the gamification platform, reflecting high acceptance of its interactive features, reward system, and ease of understanding the material. These findings demonstrate increased motivation, interest, and learning engagement among students, as well as affirming the effectiveness of gamification in supporting selfdirected learning. This study provides valuable insights for educators and platform developers in designing more engaging and effective learning experiences, while also emphasizing the importance of considering student feedback in improving learning strategies.